Pengaruh Fasilitas Dan Promosi Terhadap Minat Berkunjung Masyarakat Pada Objek Wisata Pantai Gedambaan Kabupaten Kotabaru - Andriansyah; Muhdar; Rosida; Rahmawardani (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
The method used in this study is a quantitative method using linear analysis coupled with the help of SPSS version 25. The aim is to find out how the influence of facilities and promotions on people's interest in visiting the Gedambaan Beach tourist attraction in Kotabaru Regency. The research method used is a quantitative method with a type of descriptive research. Interest in Visiting (Y) is a bound variable, while Facilities (X1) and Promotion (X2) are independent variables. The results of the study show that based on the simultaneous/joint test (test proves that all independent variables, namely the Facility (X1) and Promotion (X2) variables, there is a significant influence on the bound variable, namely the Visiting Interest variable (Y) where it is known that the Fcal value is greater than the Ftable value or 35.097 > 3.09 with a sig value. F is 0.000 which is smaller than 0.05 or 0.000 < 0.05. Based on the test on a per-sial/individual basis (t-test), it turns out that the results of the study prove that the independent variables, namely the Facility (X1) and Promotion (X2) variables, have a significant effect on the dependent variable, namely Visiting Interest (Y). Statistically, it can be concluded that the Facility and Promotion variables have a precise/individual relationship with the interest in visiting the community. Based on the test of the determination coefficient (R2), it can be concluded that Facilities (X1) and Promotion (X2) have an effect of 40.8% on the bound variable (Y), namely Visiting Interest. Meanwhile, the remaining 59.2% was influenced by other variables that were not included in the study.